THE POTENTIAL OF DEVELOPING IRAQ SMARTPHONE MARKET AS AN EMERGING AND LUCRATIVE MARKET - Ali Jarad, Ghayth (British Journal of Marketing Studies, 2014)
Smartphones importance increased day after day, in hence the market of this sector developed and becomes more powerful and lucrative. Smartphones considered as a digital oil as a description how smartphones market is powerful. Millions of devices produced by competitors with a wide range of options to face the high demand and satisfy the different needs .this paper aimed to explore the global market of smartphones and Iraq smartphones market in particular to make benchmarking to discover the gap. The result shows that Iraq market generally and smartphones market in particular unsaturated and needed to be developed by improving retails and stores, the market attractive and profitable this make it worth to be considered by companies to invest in it .